Isolats Bakteri Indigenous Penghasil Milk-Clotting Protease untuk Fermentasi Keju - Rahmani, Nanik; Sari, Yana Nurita; Palupi, Nurheni Sri; Yopi, Yopi (Perhimpunan Biologi Indonesia, 2013)
The aims of this research is to isolation of bacteria that potential to produce of milk clotting protease enzymes fromfermented food that will be used as a substitute for rennet in cheese making. There are five food fermentations suchas tauco, tempeh, red oncom, sticky tape, and pickled mustard greens that are used as a source for isolation of bacteriathat could produce milk clotting protease. The results obtained four isolates proteolytic bacteria from two fermentedfood samples, three isolates bacteria from tauco (TCN 1, TCN 2, TCN 3) and one isolate from pickledmustard greens (DSN 1). Based on 16S rDNA, these isolates were identified as Bacillus sp. Bacterial isolate TCN 1has a milk clotting activity of 29.17 U/mL, whereas bacteria isolates of TCN 2, TCN 3 and DSN 1 have activities of70 U/mL achieved at the 24 hours incubation, respectively. The proteolytic activities of bacteria isolates TCN 1,TCN 2, TCN 3 and DSN 1 at the 24 hours fermentation process were 0.0117 U/mL, 0.0021 U/mL, 0.0150 U/mL,and 0.200 U/mL, respectively. The ratio of milk clotting protease activity and the proteolytic activity for bacteriaisolates TCN 1, TCN 2, TCN 3 and DSN respectively were 5402, 175000, 7292, and 3333. This showed that theenzyme from bacterial isolates TCN 2 can be used as an alternative to rennin in cheese making.Keywords: milk clotting protease, cheese, calf rennet, fermentation food